PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. ESTADANA VENTURE CABANG KOTABUNAN SULAWESI UTARA - Susindra Katili; Heri Prasetyo (Program Studi Manajemen, 2021)
This study aims to determine the effect of compensation and work environment on job satisfaction of employees of PT. Estadana Venture, Kotabunan Branch, North Sulawesi. The type of research used in this research is quantitative research. The sample is part of the number and characteristics possessed by the population. Based on the total employee population of PT. Estadana Venture Branch Kotabunan North Sulawesi as many as 34 people, the researchers took the total population to be used as research samples. The results of this study indicate that compensation has a significant effect on job satisfaction of employees of PT. Estadana Venture Kotabunan Branch, North Sulawesi; work environment has a significant effect on job satisfaction of employees of PT. Estadana Venture Kotabunan Branch, North Sulawesi and 43.4% job satisfaction of employees of PT. Estadana Venture Branch Kotabunan North Sulawesi can be explained by the variables of compensation and work environment. While the remaining 56.6% the influence of other variables that are not in the study